Discriminating between the effect of pulse width and duty cycle on the hydrogen generation performance of 3-D electrodes during pulsed water electrolysis. (18th August 2021) - Rocha, Fernando; Proost, Joris
Abstract: The present study investigates the effect of applying voltage and current pulses during alkaline water electrolysis using 3-D Ni-based electrodes. The pulses had a square shape and alternated hydrogen production and resting time. When voltage pulses were applied, it was observed that the current at on-time was systematically higher than the current during DC electrolysis. However, during off-time, a change in polarization was observed, which decreased the overall voltage pulse performance. For pulses with a 50% duty cycle and a pulse width of 1 ms, the current response was mainly capacitive and almost no hydrogen production occurred. Current pulses on the other hand were proven to be much more promising in improving the energetic process efficiency. In that case, a pulse period of 2 ms resulted in an overpotential reduction of 17% for a 50% duty cycle. This reduction further increased to 28% when decreasing the duty cycle to 20%. Finally, in all cases where faradaic processes were dominant, applying a forced electrolyte flow was shown to be beneficial. Highlights: The current during a pulse on-time is higher than the current of DC electrolysis. During the off-time of a pulse, a change in polarization is observed. Pulses with a 50% duty cycle and widths <1 ms are mainly capacitive. Pulses with a 99% duty cycle result in an increase in average current. Forced electrolyte flow has a positive effect on faradaic pulses.